Does the addition of active body warming to in-line intravenous fluid warming prevent maternal hypothermia during elective caesarean section? A randomised controlled trial. (August 2017) - Chebbout, R.; Newton, R.S.; Walters, M.; Wrench, I.J.; Woolnough, M.
Highlights: In-line warmed intravenous fluids prevent hypothermia during caesarean section. Active body warming was not superior to in-line intravenous fluid warming. Approximately 60% of neonates were hypothermic postoperatively. Abstract: Introduction: Inadvertent perioperative hypothermia occurs frequently during elective caesarean section but perioperative active body warming is not widely used. There is a paucity of evidence of its use in the obstetric population, and no applicable guidelines. We set out to identify a superior active warming method for preventing inadvertent perioperative hypothermia. Methods: Following ethical approval, 132 women presenting for uncomplicated elective caesarean section under spinal anaesthesia were recruited. All participants received in-line intravenous fluid warming and were randomised to one of three parallel groups: no active body warming; forced air warming; and conduction mattress warming. The primary outcome was the difference in mean core temperature, measured on admission to the recovery room, between study groups. Core temperature and thermal comfort were measured perioperatively at 15-min intervals. Estimated blood loss, haemoglobin change, length of hospital stay and neonatal core temperature were also recorded. Results: One-hundred-and-thirty-one women completed the study. There was no significant difference in mean core temperature on admission to the recovery room (36.6°C vs. 36.6°C vs. 36.6°C, η 2 =0.005, P =0.74). Maternal hypothermia was prevented in all groups with only 0.3% hypothermic at any of the temperature measurements (3/1016). There was no difference in mean neonatal core temperature (36.3°C vs. 36.3°C vs. 36.3°C, η 2 =0.003, P =0.82); however, 59.4% (76/128) of all neonates were hypothermic. Conclusion: In-line intravenous fluid warming is sufficient to prevent maternal hypothermia and maintain core temperature. The addition of active body warming conferred no added benefit.